Estimating the Frequency of Hanifin and Rajka's Minor Criteria among Paediatric Atopic Cases at a Tertiary Care Hospital in Western Tamil Nadu, India- A Cross-sectional Study - K Gopalakrishnan; S Sivanandam; Sowmya S Aithal; Vinupriya Sakkaravarthi; R Prabhu Vikash; K Rajendran; S Jeevithan (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Atopic Dermatitis (AD) is a common relapsing inflammatory disorder, among the paediatric population clinically, characterised by pruritus and recurring eczematous skin lesions and a host of other cutaneous changes. Diagnosis is done on the basis of clinical findings with the usage of Hanifin and Rajka's criteria which includes 4 major and 23 minor criteria. Geographical, climatic factors and other population factors have been reported to influence the occurrence of minor criteria. Aim: To estimate the frequency of Minor criteria among paediatric atopic dermatitis in Western Tamil Nadu, India. Materials and Methods: This cross-sectional observational study was done by including 110 atopic children attending Paediatric and Dermatology Outpatient Departments (OPD) of KMCH IHSR, Coimbatore, Western Tamil Nadu, India, between March 2022 to August 2022. The clinical and ophthalmological findings were documented. Categorical variables were presented as frequency and percentages, Continuous variables were presented as Mean±Standard deviation. The data was entered in excel and was analysed using statistical package for social sciences (SPSS) version 27. Results: Among the total study population of 110, 53 (48.2%) were males and the rest 57 (51.8%) were females. The mean age was 24.73±5.18 years with a range of 2-15 years. Early age of onset was seen in 73.6% of study population. Hyperlinear palms were found in 70% of the study patients. 68.2% had Dennie Morgan infraorbital fold, 64.5% had xerosis, 61% had pityriasis alba and 60% had a family history of atopy. Conclusion: Certain minor manifestations of AD like xerosis, icthyosis, hyprerlinear palms, and perifollicular accentuation were more common in the present study. Western Tamil Nadu having a tropical semi-arid climate tempered by higher altitude could explain the differences noted in the frequency of certain minor criteria.